2016
DOI: 10.1111/pbi.12530
|View full text |Cite
|
Sign up to set email alerts
|

Co‐expression of the protease furin in Nicotiana benthamiana leads to efficient processing of latent transforming growth factor‐β1 into a biologically active protein

Abstract: SummaryTransforming growth factor beta (TGF‐β) is a signalling molecule that plays a key role in developmental and immunological processes in mammals. Three TGF‐β isoforms exist in humans, and each isoform has unique therapeutic potential. Plants offer a platform for the production of recombinant proteins, which is cheap and easy to scale up and has a low risk of contamination with human pathogens. TGF‐β3 has been produced in plants before using a chloroplast expression system. However, this strategy requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 45 publications
0
39
0
1
Order By: Relevance
“…A recent study has suggested that tissue necrosis during heterologous protein expression in planta could be linked to improper cleavage of the signal peptide. The authors reported that substituting the Arabidopsis thaliana chitinase signal peptide for the native signal sequence of transforming growth factor-b1 resulted in high levels of protein production whilst still maintaining a healthy phenotype in N. benthamiana plants (Wilbers et al, 2016). It is also worth noting that the targeting of the recombinant H5 HA protein into the plant secretory pathway resulted in the formation of enveloped VLPs which budded from the plasma membrane in the absence of other accessory proteins (D'Aoust et al, 2008).…”
Section: Targeting Recombinant Glycoproteins Into the Secretory Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has suggested that tissue necrosis during heterologous protein expression in planta could be linked to improper cleavage of the signal peptide. The authors reported that substituting the Arabidopsis thaliana chitinase signal peptide for the native signal sequence of transforming growth factor-b1 resulted in high levels of protein production whilst still maintaining a healthy phenotype in N. benthamiana plants (Wilbers et al, 2016). It is also worth noting that the targeting of the recombinant H5 HA protein into the plant secretory pathway resulted in the formation of enveloped VLPs which budded from the plasma membrane in the absence of other accessory proteins (D'Aoust et al, 2008).…”
Section: Targeting Recombinant Glycoproteins Into the Secretory Pathwaymentioning
confidence: 99%
“…Given these observations, trimeric HIV Env immunogens are often produced in mammalian cell culture by replacing the native cleavage site with a hexa-arginine motif and co-expressing heterologous furin to promote optimal cleavage of the recombinant glycoprotein (Binley et al, 2002). Furin activity does not naturally occur along the plant secretory pathway, although a precedent exists for the co-expression of the protease to produce functional human transforming growth factor b1 in planta, suggesting that theoretically it may be possible to produce cleaved HIV Env glycoproteins in plants (Wilbers et al, 2016). Another potential complication with the production of a proteolytically cleaved glycoprotein is the labile association between the respective subunits.…”
Section: Proteolytic Maturation Of Viral Glycoproteins Along the Secrmentioning
confidence: 99%
See 1 more Smart Citation
“…Current efforts to further strengthen the position of plants as valuable protein expression hosts also include the development of metabolic, cellular or phenology engineering approaches to address specific issues related to recombinant protein maturation, stability or recovery. Examples are the ectopic implementation of a dwarf plant phenotype to optimize culture area use in the greenhouse (Nagatoshi et al, 2015), activation of the octadecanoid pathway to reduce ribulose 1,5- bis -phosphate carboxylase oxygenase (Rubisco) loads in leaves prior to protein purification (Robert et al, 2015), or the expression of accessory convertases to generate biologically active forms of therapeutic proteins otherwise requiring chemical refolding after extraction (Wilbers et al, 2016). Other examples are the expression of protease inhibitors to prevent unintended protein degradation by resident proteases (Goulet et al, 2012; Pillay et al, 2014; Jutras et al, 2016), or the expression of an accessory proton channel to stabilize acid-labile and proteolysis-susceptible proteins in the Golgi lumen (Jutras et al, 2015; 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It participates in the proliferation and differentiation processes of diversified cell types, such as chondrocytes, epithelial cells and fibroblasts, and has essential regulating effects in the developing process of embryo, organs and cartilage. Studies have demonstrated that, in the chondrocytes of rabbits and cattle, TGF-β1 can regulate the synthesis of proteoglycan (4,5). In addition, TGF-β1 has the ability to promote synthesis of type II collagen by reducing consumption of proteoglycan in order to repair the cartilage (6).…”
Section: Introductionmentioning
confidence: 99%